Digital integrated dramatherapy: A feasibility study in women undergoing assisted reproductive technology - Cercato, Maria Cecilia; Pierpaoli, Sandra; Pazienza, Rosa Maria; Terrenato, Irene; Guadagnuolo, Cinzia; Cenci, Cristina; Nappi, Rossella E. (Frontiers in Psychology, 2022)
Background Dramatherapy is a practice of working and playing that uses action methods to facilitate creativity, imagination, learning, insight and growth. Methods A pilot study of Digital Integrated Dramatherapy, recruiting women from the digital community “Parole Fertili,” undergoing assisted reproductive technology. On the basis of a previous blended experience, a program based on remote sessions was conducted on a dedicated platform. Results A total of 22 women participated in the same intervention in three groups. Participants assessed the feasibility and utility of the method, both in the synchronous and asynchronous phases. The group had a fundamental role: the participants were supportive, and therapeutic benefits were due to strengthening and resilience obtained through a dialogue with other women. Using metaphors, the participants could move from the narration of the Assisted Reproductive Technology pathway to creative and corporeal expression. Conclusion The study showed that a group based on Digital Integrated Dramatherapy might help women face very difficult emotions by promoting creativity and internal resources.